Long-term prognostic value of delirium in elderly patients with acute cardiac diseases admitted to two cardiac intensive care units: a prospective study (DELIRIUM CORDIS). Issue 7 (October 2018) - Falsini, Giovanni; Grotti, Simone; Porto, Italo; Toccafondi, Giulio; Fraticelli, Aureliano; Angioli, Paolo; Ducci, Kenneth; Liistro, Francesco; Pieroni, Maurizio; Taddei, Tamara; Romanelli, Serena; Rossi, Roberto; et al.
Background: Delirium is a frequent in-hospital complication in elderly patients, and is associated with poor clinical outcome. Its clinical impact, however, has not yet been fully addressed in the setting of the cardiac intensive care unit (CICU). The present study is a prospective, two-centre registry aimed at assessing the incidence, prevalence and significance of delirium in elderly patients with acute cardiac diseases. Methods: Between January 2014 and March 2015, all consecutive patients aged 65 years or older admitted to the CICU of our institutions were enrolled and followed for 6 months. Delirium was defined according to the confusion assessment method. Results: During the study period, 726 patients were screened for delirium. The mean age was 79.1±7.8 years. A total of 111 individuals (15.3%) were diagnosed with delirium; of them, 46 (41.4%) showed prevalent delirium (PD), while 65 (58.6%) developed incident delirium (ID). Patients 85 years or older showed a delirium rate of 52.3%. Hospital stay was longer in delirious versus non-delirious patients. Patients with delirium showed higher in-hospital, 30-day and 6-month mortality compared to non-delirious patients, irrespective of the onset time (overall, ID or PD). Six-month re-hospitalisation was significantly higher in overall delirium and the PD group, as compared to non-delirious patients. Kaplan–Meier analysis showed a significant reduction of 6-month survival in patients with delirium compared to those without, irrespective of delirium onset time (i.e. ID or PD). A positive confusion assessment method was an independent predictor of short and long-term mortality. Conclusions: Delirium is a common complication in elderly CICU patients, and is associated with a longer and more complicated hospital stay and increased short and long-term mortality. Our findings suggest the usefulness of a protocol for the early identification of delirium in the CICU. Clinicaltrials.gov: NCT02004665